Effect of Cigarette Smoking On Blood Lipids a A Study in Belgaum, Northern Karnataka, India (Global Journal of Medical Research, 2012)
Cigarette smoking is an important and independent risk factor of atherosclerosis, coronary artery disease and peripheral vascular disorders. Apart from active smokers, passive-smokers are also prone for the development of smoking related disorders. Smoking adversely affects the concentration of the plasma lipids and lipoprotein levels. The lipid profile was measured from 100 selected smokers and nonsmokers and the study shows that as the intensity and duration of smoking increases a significant increase in the levels of very low density lipoprotein -cholesterol, low density lipoprotein -cholesterol, triglyceride and total cholesterol are noted in almost all groups of cigarette smokers as compared to nonsmokers. Simultaneously a significant reduction in the level of High density lipoprotein-cholesterol is observed in cigarette smokers as the intensity and duration is increased. These findings add another health enhancing benefit by the cessation of smoking.
Keywords: Cigarette smoking; Triglyceride; low density lipoprotein cholesterol; very low density lipoprotein cholesterol; High Density lipoprotein cholesterol